2006
DOI: 10.21273/horttech.16.2.0205
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting Responses and Economics of Containerized and Bare-root Strawberry Transplants Established with Different Irrigation Methods

Abstract: Strawberry (Fragaria ×ananassa) crops were transplanted in two seasons in central Florida with bare-root and containerized (plug) plants under three transplant establishment-period irrigation methods to evaluate crop fruiting responses and production economics associated with the various establishment systems. Irrigation was not required to establish plug transplants in the field. Early (first 2 months) fruit yield with nonirrigated plug plants was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
1
19
0
2
Order By: Relevance
“…The containerized and bare-rooted plants produced similar-sized fruit on the Sunshine Coast over 4 years, in agreement with the results reported in Florida. For instance, Hochmuth et al (2006) found that average fruit fresh weight ranged from 14.3 to 15.9 g in bare-rooted and containerized plants under sprinkler irrigation over 2 years at Dover. In contrast, the experience in California is that containerized plants sometimes produced small fruit (Larson et al, 2002).…”
Section: Time Of Plantingmentioning
confidence: 99%
See 2 more Smart Citations
“…The containerized and bare-rooted plants produced similar-sized fruit on the Sunshine Coast over 4 years, in agreement with the results reported in Florida. For instance, Hochmuth et al (2006) found that average fruit fresh weight ranged from 14.3 to 15.9 g in bare-rooted and containerized plants under sprinkler irrigation over 2 years at Dover. In contrast, the experience in California is that containerized plants sometimes produced small fruit (Larson et al, 2002).…”
Section: Time Of Plantingmentioning
confidence: 99%
“…Our experiments differed from the research conducted in Florida where the containerized plants were generally obtained from nurseries at high elevation or from high latitude in North Carolina (Gilreath et al, 2006;Hochmuth et al, 2006) or Minnesota (Kokalis-Burelle, 2003). These areas are up to 10°C cooler than Florida in summer.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have evaluated the performance of out-of-state conditioned SP in comparison with BR in Florida (Bish et al, 1997(Bish et al, , 2003Cantliffe et al, 2007 et al, 2006a, 2006bSouthwest Florida Water Management District, 2000). However, few researchers have evaluated the response of unconditioned Florida-produced SP to time in nursery before field transplanting.…”
mentioning
confidence: 99%
“…Between 8 and 14 hÁd -1 of continuous sprinkler irrigation are used to reduce the air temperature around the strawberry crown and keep leaves moist (Bish and Cantliffe, 2002;Bish et al, 1997). This irrigation practice accounts for one third of the total water required by the crop throughout the season (Hochmuth et al, 2006a), and it can impact the crop negatively by increasing disease dissemination and leaching nutrients out of the rooting zone (Bish et al, 1997;Hochmuth et al, 2006b). Lack of uniformity of bare-root transplants combined with plant damage created by sprinkler irrigation can contribute to reduction of early yield (Bish et al, 2001).…”
mentioning
confidence: 99%